Rejecting Wraparound Support: An Ethnographic Study of Social Service Provision. (6th June 2017) - Parsell, Cameron; Stambe, Rose; Baxter, Janeen
Abstract: Social work rarely considers how the delivery of social services shape the behaviours of, and potentially creates dependencies for, people receiving services. Drawing on an ethnographic examination, this article presents the Gain model as a theory and a practice. Delivered in temporary homeless accommodation, the Gain model rejects wraparound service provision. Premised on service users as people rather than clients, it challenges the idea that more social services are required to assist people experiencing material deprivation. The article outlines two contributions to social work. First, it challenges social work to develop a clear narrative about people with the desire and potential to live optimistically aspirational lives. Second, the article puts forward a view of an autonomous good life that is at odds with the conditions and even resources associated with accessing social services. Rather than practising to disrupt oppression, the Gain model pushes social work to think about how providing services to excluded groups is premised on limited life expectations. The model's value lies in the significance of a reflective practice premised on people using social work services as no different to the social workers providing the services.